Development of Huff curves for peninsular Malaysia - Azli, M.; Rao, A.R. (Elsevier, 2010)
Huff curves are commonly used in drainage design The basic objective of the present paper is to report about the development of Huff curves for Peninsular Malaysia. Hourly rainfall data from 13 stations in Peninsular Malaysia were used in the study Data from about 5800 storms were divided into quartile storms to derive the Huff curves. A comparison of Huff curves using correlation coefficients revealed that the Huff curves from different stations are very similar to each other. The Huff curves from the 13 stations were averaged to derive the Huff curves for Peninsular Malaysia The Huff curves from the United States are partially similar to those from Peninsular Malaysia in the sense that Huff curves for some quartiles are close to each other whereas they are not for others. The rainfall information presently used for design in Malaysia is very dissimilar to the Huff curves derived in this study. (C) 2010 Elsevier B.V. All rights reserved.